Behavioral and neurophysiological correlates of emotional face processing in borderline personality disorder: are there differences between men and women? - Andermann, Martin; Izurieta Hidalgo, Natalie A.; Rupp, André; Schmahl, Christian; Herpertz, Sabine; Bertsch, Katja (European archives of psychiatry and clinical neuroscience, 2022)
Emotional dysregulation is a core feature of borderline personality disorder (BPD); it is, for example, known to influence one’s ability to read other people’s facial expressions. We investigated behavioral and neurophysiological foundations of emotional face processing in individuals with BPD and in healthy controls, taking participants’ sex into account. 62 individuals with BPD (25 men, 37 women) and 49 healthy controls (20 men, 29 women) completed an emotion classification task with faces depicting blends of angry and happy expressions while the electroencephalogram was recorded. The cortical activity (late positive potential, P3/LPP) was evaluated using source modeling. Compared to healthy controls, individuals with BPD responded slower to happy but not to angry faces; further, they showed more anger ratings in happy but not in angry faces, especially in those with high ambiguity. Men had lower anger ratings than women and responded slower to angry but not happy faces. The P3/LPP was larger in healthy controls than in individuals with BPD, and larger in women than in men; moreover, women but not men produced enlarged P3/LPP responses to angry vs. happy faces. Sex did not interact with behavioral or P3/LPP-related differences between healthy controls and individuals with BPD. Together, BPD-related alterations in behavioral and P3/LPP correlates of emotional face processing exist in both men and women, supposedly without sex-related interactions. Results point to a general ‘negativity bias’ in women. Source modeling is well suited to investigate effects of participant and stimulus characteristics on the P3/LPP generators.
Gesehen am 22.05.2023